The studies on virus isolation from feces in calves - Sibel Yavru; Atilla Şimşek (Eurasian Journal of Veterinary Sciences)
In this study, 100 feces samples from 0-1 old year calves with clinical sign of respiratory and digestive systems, fever and acut diarrhae symptom in eight private managements of Konya and its arround were used for virus isolation studies in sensitive cell cultures and checked for BAV 1,2 and 3. As a result of inoculation of 100 feces samples onto foetal calf kidney cell cultures, 2 viruses were isolated. The isolated viruses were identified as BAV-1 by cross microneutralization test with rabbit hyperimmun sera. Blood serum samples from these animals were tested using microneutralization test tor neutralizing antibody to BAV 1, 2 and 3. The presence of neutralizing antibody was detected in 17 out of 100 blood sera (17%) against BAV-1, in 21 (21%) against BAV-2 and in 23 (23%) against BAV-3. Serum neutralization 50 (SNso) values of seropositive animals were detected to be 1/14.1-1/531, 1/14.1-1/316 and 1/ 14.1-1/531 for BAV-1,2 and 3 respectively.